Age-related macular degeneration associated polymorphism rs10490924 in ARMS2 results in deficiency of a complement activator. Issue 1 (December 2017) - Micklisch, Sven; Lin, Yuchen; Jacob, Saskia; Karlstetter, Marcus; Dannhausen, Katharina; Dasari, Prasad; von der Heide, Monika; Dahse, Hans-Martin; Schmölz, Lisa; Grassmann, Felix; Alene, Medhanie; Fauser, Sascha; et al.
Abstract Background Age-related macular degeneration (AMD) is the leading cause of blindness in developed countries. The polymorphism rs10490924 in theARMS2 gene is highly associated with AMD and linked to an indel mutation (del443ins54), the latter inducing mRNA instability. At present, the function of the ARMS2 protein, the exact cellular sources in the retina and the biological consequences of the rs10490924 polymorphism are unclear. Methods Recombinant ARMS2 was expressed inPichia pastoris, and protein functions were studied regarding cell surface binding and complement activation in human serum using fluoresence-activated cell sorting (FACS) as well as laser scanning microscopy (LSM). Biolayer interferometry defined protein interactions. Furthermore, endogenousARMS2 gene expression was studied in human blood derived monocytes and in human induced pluripotent stem cell-derived microglia (iPSdM) by PCR and LSM. The ARMS2 protein was localized in human genotyped retinal sections and in purified monocytes derived from AMD patients without the ARMS2 risk variant by LSM. ARMS2 expression in monocytes under oxidative stress was determined by Western blot analysis. Results Here, we demonstrate for the first time that ARMS2 functions as surface complement regulator. Recombinant ARMS2 binds to human apoptotic and necrotic cells and initiates complement activation by recruiting the complement activator properdin. ARMS2-properdin complexes augment C3b surface opsonization for phagocytosis. We also demonstrate for the first time expression of ARMS2 in human monocytes especially under oxidative stress and in microglia cells of the human retina. The ARMS2 protein is absent in monocytes and also in microglia cells, derived from patients homozygous for theARMS2 AMD risk variant (rs10490924). Conclusions ARMS2 is likely involved in complement-mediated clearance of cellular debris. As AMD patients present with accumulated proteins and lipids on Bruch's membrane, ARMS2 protein deficiency due to the genetic risk variant might be involved in drusen formation.